The Influence of Learning Outcomes of PKK Subjects and Family Environment on Entrepreneurial Interests of Culinary Department Students at SMK Widya Praja Ungaran - Fatimah, Cikha Yulia; Saptariana (Jurnal Sains Boga, 2025)
SMK is vocational school that aims to prepare students to enter the world of entrepreneursip and industry. The entrepreneurship subject that can increase student’s interest in entrepreneurship is PKK subject. Student’s interest in entrepreneurship can also be influenced by te family environment. The purpose of this study was to determine the effect of learning outcomes in PKK subjects and the family environment on the interest in entrepreneurship of class XI students majoring in Culinary partially and simultaneously. This tsudy uses a causal associative research type with independent variabels is learning outcomes in PKK subjects and te family environment, the dependent variable is student’s interest in entrepreneurship. The population of this study was class XI students majoring in Culinary in the SMK Widya Praja Ungaran and using total sampling of 49 students. Data collection techniques usaed documentation and questionnaires. Data anaysis using simple linear regression analysis, multiple linear regression, and coefficient of determination. The results showed that the learning outcomes of PKK subjects had a significant effect on students’ interest in entrepreneurship with a significance value of 0.009<0.05 and a coefficient of determination is 13.6%. There was a significant influence of the family environment on students’ interest in entrepreneruship with a significance value of 0.000<0.05 and a coefficient of determination is 48.7%. Simultaneously, the learning outcomes of PKK subjects and the family environment had a positive and significant effect on students’ interest in entrepreneurship with a significance value of 0.000<0.05 and fcount 26,852>3,20 and a coefficient of determination is 53.9%.